2006
DOI: 10.1111/j.1523-1739.2005.00318.x
|View full text |Cite
|
Sign up to set email alerts
|

A Nationwide Assessment of the Biodiversity Value of Uganda's Important Bird Areas Network

Abstract: BirdLife International's Important Bird Areas (IBA) program is the most developed global system for identifying sites of conservation priority There have been few assessments, however, of the conservation value of IBAs for nonavian taxa. We combined past data with extensive new survey results for Uganda's IBAs in the most comprehensive assessment to date of the wider biodiversity value of a tropical country's IBA network. The combined data set included more than 35,000 site x species records for birds, butterf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 21 publications
1
17
0
Order By: Relevance
“…First, we regressed species richness on each environmental variable with sample area as a second independent variable, calculated partial coefficient of determination for each of the two independent variables (Quinn and Keough 2002), adjusted the partial coefficient of determination for each independent variable proportionally in order to achieve the equality between the sum of partial coefficients of determination of the two independent variables and the coefficient of determination for the regression, and then calculated the correlation coefficient between species richness and the environmental variable based on the adjusted partial coefficient of determination for the environmental variable (we denoted it as r partial ). Second, we followed previous authors (Howard et al 1998, Patten 2004, Lamoreux et al 2006, Tushabe et al 2006) to statistically remove locality area effect before we conducted correlation analyses. Specifically, we regressed species richness on locality area, and then calculated correlation coefficient between the residuals of species richness and each environmental variable (we denoted this type of correlation coefficients as r residual ).…”
Section: Methodsmentioning
confidence: 99%
“…First, we regressed species richness on each environmental variable with sample area as a second independent variable, calculated partial coefficient of determination for each of the two independent variables (Quinn and Keough 2002), adjusted the partial coefficient of determination for each independent variable proportionally in order to achieve the equality between the sum of partial coefficients of determination of the two independent variables and the coefficient of determination for the regression, and then calculated the correlation coefficient between species richness and the environmental variable based on the adjusted partial coefficient of determination for the environmental variable (we denoted it as r partial ). Second, we followed previous authors (Howard et al 1998, Patten 2004, Lamoreux et al 2006, Tushabe et al 2006) to statistically remove locality area effect before we conducted correlation analyses. Specifically, we regressed species richness on locality area, and then calculated correlation coefficient between the residuals of species richness and each environmental variable (we denoted this type of correlation coefficients as r residual ).…”
Section: Methodsmentioning
confidence: 99%
“…This has previously been shown for patterns of a diversity both at the local level (Lawton et al 1998, Schulze et al 2004, Favreau et al 2006, Wolters et al 2006) and on regional to continental scales (Beccaloni and Gaston 1995, Carroll and Pearson 1998, Myers et al 2000, Moore et al 2002, Tushabe et al 2006, Billeter et al 2008). We also found that different approaches to calculating a diversity (species numbers vs. differences between species numbers; observed vs. estimated values) resulted in roughly similar values.…”
Section: Implications For Biodiversity Samplingmentioning
confidence: 96%
“…In the tropics, the congruence of diversity patterns between different taxa has mostly been studied across large geographical regions (e.g., Beccaloni and Gaston 1995, Carroll and Pearson 1998, Oliver et al 1998, Myers et al 2000, Moore et al 2002, Duque et al 2005, Tushabe et al 2006, Larsen et al 2007, McKnight et al 2007. Only four studies have compared small-scale changes in taxonomically diverse groups along gradients of land use within tropical landscapes (Lawton et al 1998, Schulze et al 2004, Barlow et al 2007, No¨ske et al 2008; see Plate 1).…”
Section: Introductionmentioning
confidence: 99%
“…There are a few published papers quantitatively documenting the diversity of butterflies for some agricultural regions in East Africa. In Uganda, most of the works on butterflies have been carried out mainly in natural areas, forest ecosystems and in protected areas (Tumuhimbise et al 1998;Howard et al 2000;Molleman et al 2006;Tushabe et al 2006). There exist no published data describing extensively the diversity of butterflies found in agricultural landscapes in Uganda in relationship to climatic, regional, landscape and local drivers.…”
Section: Introductionmentioning
confidence: 99%